2001
DOI: 10.1161/01.cir.103.23.2851
|View full text |Cite
|
Sign up to set email alerts
|

Phase 2 Early Afterdepolarization as a Trigger of Polymorphic Ventricular Tachycardia in Acquired Long-QT Syndrome

Abstract: This study provides the first direct evidence from intracellular action potential recordings that phase 2 EAD can be generated from intact ventricular wall and produce a trigger to initiate the onset of TdP under QT prolongation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
212
2
3

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 255 publications
(229 citation statements)
references
References 14 publications
12
212
2
3
Order By: Relevance
“…This accuracy of repolarization time measurement is important in the study of arrhythmogenic mechanisms because it is the heterogeneity of instantaneous local repolarization that underlies phase 2 reentry and initiation of ventricular arrhythmias. 3,18 In agreement with Chen et al, 12 the Wyatt method considerably underestimates ARI for the positive T wave in our report, despite a good correlation with MAP90% (rϭ0.86). With this method, the error between MAP90% and ARI for the positive T wave was Ϫ47Ϯ12 ms.…”
Section: Discussionsupporting
confidence: 92%
“…This accuracy of repolarization time measurement is important in the study of arrhythmogenic mechanisms because it is the heterogeneity of instantaneous local repolarization that underlies phase 2 reentry and initiation of ventricular arrhythmias. 3,18 In agreement with Chen et al, 12 the Wyatt method considerably underestimates ARI for the positive T wave in our report, despite a good correlation with MAP90% (rϭ0.86). With this method, the error between MAP90% and ARI for the positive T wave was Ϫ47Ϯ12 ms.…”
Section: Discussionsupporting
confidence: 92%
“…This characteristic of the rabbit ventricle, particularly in female gender, renders it exceptionally sensitive even to weak QT prolonging agents. 2,7,8,27 In the present study, a positive signal for QT prolongation was observed for all drugs with a known TdP risk, even for drugs that tested negative in other preclinical models. For example, terfenadine, a non-cardiac drug with a TdP risk in humans, caused little QT or action potential prolongation in conscious dogs, 28 or in isolated canine Purkinje fibers, 29 porcine myocardium or Purkinje fibers, 30 but prolonged QT interval by more than 20% in the rabbit left ventricular wedge preparation and increased dispersion of repolarization by nearly 50%.…”
Section: Discussionsupporting
confidence: 48%
“…6 From a mechanistic point of view, other factors, such as dispersion of repolarization, have been shown to contribute to the development of TdP. 5,[7][8][9] There are a number of in vitro and in vivo experimental models available for the preclinical assessment of the TdP potential of new agents. However, few have been validated in a blinded fashion for their positive and negative predictive value.…”
Section: Introductionmentioning
confidence: 99%
“…EADs are thought to be generated by the recovery and reactivation of ICa L (window Ca 2+ current) and / or the late sodium current as a result of incomplete inactivation of sodium channels during the prolonged APD (Volders et al, 2000;Zeng et al, 1995). The combination of an increased dispersion of repolarisation creating a substrate for reentry and EADs triggering reactivation of non-refractory tissue may lead to functional reentry and Torsades de Pointes (TdP) (Antzelevitch et al, 2006;Yan et al, 2001). The term 'Torsades de Pointes', which in English means 'twisting of the points', was originally coined by Desertenne in 1966 as a description of the irregular change in polarity of the QRS complexes of the surface ECG during tachycardia (Desertenne, 1966).…”
Section: Mechanisms Of Class III Induced Proarrhythmiamentioning
confidence: 99%